A systematic review of design factors to prevent attrition and dropout in e-Learning courses - Monteiro, Sandro (2017)
The problem with high rates of attrition in e-Learning courses has been argued over at length without a clear understanding of what factors contribute to learners dropping out, withdrawing or not completing e- Learning courses. The available research suggests that attrition among adult online learners can be classified into two broad categories: (i) factors related to the learner and his/her context, and (ii) factors related to the course design. ‘Better e-Learning for All’, an Erasmus+ Strategic Partnership project for adult education, aims to enhance the knowledge about e-Learning as a primary environment for adult education. Thus, the partnership has been studying the e-Learning dropouts and dropout reasons reported in literature in order to identify a suitable ‘state-of-the- art’ concerning dropout and attrition: this chapter presents the review process and the data obtained.